Pengembangan Paket Instruksional (Abero) untuk Meningkatkan Perilaku Adaptif Peserta Didik Era New Normal Pandemi Covid-19 - Woro Tien Asrini Putri; Rusdi Rusdi (Bioscientist : Jurnal Ilmiah Biologi, 2022)
This research aims to develop learning packages study in the new normal era in increasing students' adaptive behavior. R & D development research, which includes research activities carried out to obtain information about user needs while development activities are carried out to produce learning tools. By involving n = 106 students for the treatment group and 106 students for the control group. ABERO product development is measured by providing pre-scaling and post-scaling instruments with 17 items which are empirically valid and have a reliability of 58.52%. The hypothesis was tested in exploratory form using the dependent t-test and independent t-test at α = 0.05. Based on the results of the independent t-test, a t-test result of 3.532 was obtained which was very significant in explaining the difference in the difference in the scores being compared, namely between gain-scores. This differences is very significant means that the product that students read and study is very effective in increasing (pre-score to post-scaling score = gain-scores) their adaptive behavior. Therefore, if students' adaptive behavior can be improved, then this instructional package is beneficial to implement. This is one of the efforts to increase adaptive behavior by introducing them to basic knowledge about the Covid-19 pandemic and moral messages.